The conceptual models and mechanisms of action that underpin advance care planning for cancer patients: A systematic review of randomised controlled trials. (January 2019) - Lin, Cheng-Pei; Evans, Catherine J; Koffman, Jonathan; Armes, Jo; Murtagh, Fliss E M; Harding, Richard
Background: No systematic review has focused on conceptual models underpinning advance care planning for patients with advanced cancer, and the mechanisms of action in relation to the intended outcomes. Aim: To appraise conceptual models and develop a logic model of advance care planning for advanced cancer patients, examining the components, processes, theoretical underpinning, mechanisms of action and linkage with intended outcomes. Design: A systematic review of randomised controlled trials was conducted, and was prospectively registered on PROSPERO. Narrative synthesis was used for data analysis. Data sources: The data sources were MEDLINE, CINAHL, PsycINFO, EMBASE, CENTRAL, PROSPERO, CareSearch, and OpenGrey with reference chaining and hand-searching from inception to 31 March 2017, including all randomised controlled trials with advance care planning for cancer patients in the last 12 months of life. Cochrane quality assessment tool was used for quality appraisal. Results: Nine randomised controlled trials were included, with only four articulated conceptual models. Mechanisms through which advance care planning improved outcomes comprised (1) increasing patients' knowledge of end-of-life care, (2) strengthening patients' autonomous motivation, (3) building patients' competence to undertake end-of-life discussions and (4) enhancing shared decision-making in a trustful relationship. Samples were largely highly educated Caucasian. Conclusion: The use of conceptual models underpinning the development of advance care planning is uncommon. When used, they identify the individual behavioural change. Strengthening patients' motivation and competence in participating advance care planning discussions are key mechanisms of change. Understanding cultural feasibility of the logic model for different educational levels and ethnicities in non-Western countries should be a research priority.